2019
DOI: 10.1038/s41598-019-55367-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient patterns and the skeletal muscle mass index among Polish women: a cross-sectional study

Abstract: Ageing involves significant changes in skeletal muscle mass and its functioning. This study aimed to identify the major nutrient patterns (NPs) present in a sample of adult Polish women and evaluate their associations with the skeletal muscle mass index (SMI). A cross-sectional study initially recruited 527 women, and a final analysis was carried out on 275 women aged 32–60 years. Nutrient intake was assessed using fourteen repetitions of 24-hour dietary recall. NPs were derived using principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to the latest studies, a higher basal metabolic rate is a biomarker of healthy aging [53]. A comparison of the present findings with the results of a study conducted on a large cohort of healthy middle-aged women and men revealed that Master swimmers were characterized by lower values of BMI, body fat mass, waist-to-hip ratio, and body fat percentage than untrained peers [54,55]. Our study did not reveal sarcopenia risk in Master athletes.…”
Section: Discussionsupporting
confidence: 67%
“…According to the latest studies, a higher basal metabolic rate is a biomarker of healthy aging [53]. A comparison of the present findings with the results of a study conducted on a large cohort of healthy middle-aged women and men revealed that Master swimmers were characterized by lower values of BMI, body fat mass, waist-to-hip ratio, and body fat percentage than untrained peers [54,55]. Our study did not reveal sarcopenia risk in Master athletes.…”
Section: Discussionsupporting
confidence: 67%
“…Skeletal muscle is one of the main organs in the body that performs various functions, such as protecting bones, providing muscle strength, and is important for maintaining health (Danielewicz et al., 2019 ). Nutrients, including proteins, are among the most important factors in maintaining skeletal muscle (Chanet et al., 2017 ; Hamarsland et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%